A Strategic Framework for Business Model Pivot and Value Co-Creation: Evidence from Traditional Travel Agencies in Indonesia - Isyanto, Puji; Yosepha, Sri Yanthy; Arina, Ida (Integrasi Sains Media, 2026)
This study examines the strategic mechanisms that drive traditional travel agencies to pivot their business models in response to relentless digital disintermediation. By integrating Service-Dominant (S-D) Logic and Dynamic Capabilities theory, the research evaluates how internal orientations and collaborative processes enable traditional intermediaries to reclaim market relevance as Experience Architects. Using a quantitative research design, data were collected from 200 owners, directors, and senior managers of traditional travel agencies across Indonesia's primary tourism hubs. To ensure statistical rigor, the sample size was validated using G*Power 3.1, confirming its adequacy for detecting medium effect sizes within the complex structural model. The proposed structural model was assessed using Partial Least Squares Structural Equation Modeling (SEM-PLS), supplemented by an Importance-Performance Map Analysis (IPMA) to identify critical strategic priorities. The results demonstrate that while Digital Capability serves as a necessary operational foundation, it is not the primary driver of a strategic transformation. Instead, Value Co-Creation and Strategic Flexibility are found to be the dominant catalysts for a successful Business Model Pivot. Specifically, Value Co-Creation exerts a substantial influence, reinforcing the argument that a successful pivot is a relational achievement rooted in human-tech synergy rather than a purely technological one. Furthermore, the results confirm that a structured Business Model Pivot leads to a significant and sustained Competitive Advantage. This research contributes to the tourism management literature by providing a novel framework that bridges entrepreneurial intent with co-creative execution. It offers a practical roadmap for traditional travel agencies to transition from legacy ticketing brokers to specialized experience architects within a smarter tourism ecosystem.